Computerized Tomography (CT) Liver Attenuation Index Versus Coronary Calcium Score as Predictors of Coronary Artery Diseases among patients examined with Coronary Computed Tomographic Angiography - Imad Hussein Salman Al-Kufaishi; Riyadh W. AL-Esawi; Ahmed Kadhim Abbass Al-Kelabi (Academic Journal of Clinicians, 2022)
Liver attenuation index (LAI) used as a predictor of hepatic steatosis . Several previous studies and literatures tried to correlate between steatosis and coronary artery disease, hence we aimed to evaluate validity of liver attenuation indexas a predictor of coronary artery disease compared to coronary calcium score . We conducted a cross-sectional study included 100 adult patients who met the inclusion criteria and referred to the multi detector computed tomographic unit in faculty of medicine Kufa university Iraq , between July 2019 to end of January 2020 . Calcium score and LAI are measured in unenhanced study and we compared the results with the coronary computed tomographic angiographic findings. Our data analysis revealed that revealed 21 steatotic patients, 41patients with calcification was more frequentin steatotic than non-steatotic cases, 4..6% and 39.2%, respectively. Liver attenuation index showed low sensitivity (44%),fair specificity of (62%), low accuracy (58%), in prediction of significant angiographic findings. CAC score a .8%sensitivity, 89% specificity and 84% accuracy (84%). In conclusion Liver attenuation index had no significant prediction of coronary artery disease. Coronary calcium score was a good predictor of coronary artery disease. So we recommend continue using coronary calcium score in assessment of patients with coronary artery disease.